Positional Variation of the Infraorbital Foramen in Caucasians and Black Africans from Britain: Surgical Relevance and Comparison to the Existing Literature. Issue 3 (May 2021) - Aseem, Rabiya; Scantling-Birch, Yarrow; Naveed, Hasan; Gore, Sri; Messiha, Ashraf; Rajak, Saul; Davagnanam, Indran
Abstract : Background: Midface augmentation and orbital surgery carry an inherent risk of injury to the infraorbital vascular bundle, especially the infraorbital nerve where it exits the infraorbital foramen (IOF). This can result in significant morbidity for the patient, including paresthesia and neuralgia. Studies report significant heterogeneity in IOF position according to gender, ethnicity, and laterality. A knowledge of the relationship of the IOF to regional soft tissue, bony landmarks, and its variation among ethnicities is likely to reduce iatrogenic injuries. Methods: A single-center retrospective computed tomography (CT)-based study was conducted. Twenty Caucasians and 20 Black Africans patients were selected from an existing radiologic database at Moorfields Eye Hospital, London, UK. DICOM image viewing software (Syngo, Siemens Healthineers) was used to record the position of the IOF using standardized sagittal and axial views. Results: There was a statistically significant difference in the horizontal position of the IOF in the 2 races ( P = 0.00). The combined measurements were used to derive a rectangular zone of variability measuring 14.30 mm by 10.60 mm. This zone was found to lie 3.50 mm below the infraorbital rim, 7.10 mm medial to the piriform aperture, and 11.60 mm from the lateral orbital rim. Conclusion: A sound knowledge of key facial landmarks is necessitated when performing midface augmentation and orbital surgery. An anatomical safe zone depicting the variation of the IOF will help reduce iatrogenic injury to the infraorbital nerve and prevent patient morbidity. Abstract : Supplemental Digital Content is available in the text